2014
DOI: 10.4103/0975-7406.137395
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of dental age, bone age, and chronological age in the human immunodeficiency virus positive children

Abstract: Background and Objective:The knowledge of bone age and dental age is of great importance for pediatrician and pediatric dentist. It is essential for pediatric dentist to formulate treatment plan and it is a source of complementary information for pediatrician. There are few studies in literature, which showed the relationship between dental age, bone age and chronological age in HIV-positive children. Therefore, objective of this study was to determine and compare dental age, bone age and chronological age in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…It is possible these children will experience some 'catch-up' skeletal maturation on initiation of puberty, which may be more rapid in duration than individuals who are more advanced in maturation at the same age. The 6-month delay is less than that seen in Brazilian and Indian CWH on ART, aged 5-11 and 8-14 years respectively, who had an SMD of over one year, though these studies were smaller and did not include older adolescents, nor in India a comparator group [10,11].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…It is possible these children will experience some 'catch-up' skeletal maturation on initiation of puberty, which may be more rapid in duration than individuals who are more advanced in maturation at the same age. The 6-month delay is less than that seen in Brazilian and Indian CWH on ART, aged 5-11 and 8-14 years respectively, who had an SMD of over one year, though these studies were smaller and did not include older adolescents, nor in India a comparator group [10,11].…”
Section: Discussionmentioning
confidence: 84%
“…Skeletal maturation is in uenced by several factors such as genetic ancestry and environmental factors like socio-economic deprivation, nutritional status (e.g., vitamin D and calcium intake), physical activity and co-morbid disease [4,6,9]. Studies have suggested that CWH may have delayed skeletal maturation despite ART [10,11]; however, none have been conducted in sub-Saharan Africa where the majority of CWH live. Given the impact of maturation on achieving genetic potential and consequently future health, it is important to understand how skeletal development progresses through puberty in males and females from sub-Saharan Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Presently, the dental age and skeletal development stage are used as the main indices of skeletal growth and maturation in dental practice [ 19 ]. These two variables are more valuable in clinical assessments than chronological age and gender-related characteristics [ 11 ]. Vitamin D plays a fundamental role in the development, metabolism, and function of hard tissues; therefore, its deficiency contributes to growth retardation [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, no study was previously designed to assess the development of the CV in HIV patients. The available scientific literature is scarce and focuses on the radiographic assessment of the hand and wrist ( 21 , 22 ), the teeth ( 19 , 22 , 23 ) and the craniofacial bones ( 18 ). In the clinical practice, information on the skeletal development of HIV infected children through the CV is relevant for any therapeutic approach that requires that analysis and the prediction of growth.…”
Section: Discussionmentioning
confidence: 99%